Is inequality always unfair? Experimental evidence on preferences for redistribution in Mozambique and Viet Nam - Ines A. Ferreira; Rachel M. Gisselquist; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2025)
Knowledge of the factors driving people's views on redistribution in the Global South remains limited. While these societies occupy top positions in inequality rankings, redistribution levels tend to be lower. We combine survey and experimental data from Mozambique and Viet Nam to test whether redistributive preferences vary depending on the source of inequality, focusing on two channels, fairness views and communication. First, we confirm the finding that inequality resulting from differences in merit is more accepted than inequality due to luck or factors outside of individual control. We also observe heterogeneity in fairness views. Second, we extend the analysis to consider whether allowing for communication between a receiver, who can suggest a distribution, and a dictator, who makes the final decision, affects redistribution preferences. We find that the relevance of the source of inequality remains. However, whether the expectation of the receiver is met by the dictator varies across samples and depends on the source of inequality. Overall, our results provide important insights into the universality of fairness views and point to the need for more analysis across contexts with different institutional and economic backgrounds.
Keywords: C93; D31; D63; D90; 330; inequality; fairness; preferences for redistribution; Mozambique; Viet Nam